PASSIVITY TO PERFORMATIVITY OF SACRED MOUNTAINS OF JE TSONGKHAPA AND MAHAKALA (GONBO) IN THE LUNGNAK VALLEY OF LADAKH: CONTEMPLATING THE CONTEMPORANEITY OF EPITOMES OF PAREIDOLIA (IN INDIA) - Wangmo, Kalsang; M., Ramakrishnan; Tsetan, Stanzin (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Pareidolia is an interesting concept that gives a wide scope for understanding the complex relationship between culture, society, and landscapes. It is not merely a perception of human images or objects on natural entities, rather it is an establishment of cultural relation or relatedness with the perceived objects through a “tendency to perceive a connection or meaningful pattern between two unrelated things” Robert (2017), cf. https://en.wikipedia.org/wiki/Apophenia) - technically known as apophenia. Pareidolia is defined as “tendency to perceive a specific, often meaningful image in a random or ambiguous visual pattern [and] […] the human ability to see shapes or make pictures out of randomness” (Pamela Ferdinand, Merriam-Webster,:2023, www.merriam-webster.com/dictionary/pareidolia ), or as “imagined perception of a pattern or meaning where it does not actually exist” (Collins Dictionary, 2023, www.collinsdictionary.com/dictionary/english/pareidolia), and or as “our brains are wired to look for faces in objects, calling the phenomenon pareidolia” (Buffins in The Sun (2012), Quoted in Collins, https://www.collinsdictionary.com/sentences/english/pareidolia). Although these perceptions are founded upon the ‘self-referential over-interpretations of actual sensory perceptions’ Robert (2017), cf. https://en.wikipedia.org/wiki/Apophenia), their significant role for community’s spiritual life is inevitable as they transform natural things into tangible objects to be protected as part of their cultural heritage with esoteric values. Interestingly, a lot of artistic and aesthetic elements of the local communities could be seen reflected in these perceptions which are also best-known examples of elegant craft culture associated with different genres of folklore including myths, stories, beliefs, customary practices, materials culture, etc., that together constitute the folklife in a particular environmental setting. However, by referring to the self-evolved sacred landscapes of Je Tsongkhapa and Mahakala Gonbo of Lungnak valley in Ladakh region, this article delineates the artistic, aesthetic, and spiritual life associated with the splendorous and magnificent mountains that emerge to shed their passivity to acquire performativity for giving a new dimension to human life. Based on the data collected through observation method, case study and extensive interviews, this article also explores the nature and significance of the performative status of natural objects for future generations through their constant guidance, support and preaching of moral and ethical values that are indispensable in the globalized context. Finally, this article is an attempt to expand the horizon of literature and its concepts to contemplate things around us in the forms of tangible and intangible heritages which necessitate interdisciplinary tools.